PWE-031 How Long is The Pre-Clinical Phase of Crohn's Disease: Clues from Adult Height Measurements. (17th August 2016) - Clough, J; Mendall, M; Braim, D; Hong, A
Abstract : Introduction: Inflammatory bowel disease (Crohns disease more than ulcerative colitis) is known to affect growth and final adult height when diagnosed before the end of puberty. Onset after the growth period has stopped would not be expected to have an effect on peak adult height unless there were pre-clinical changes in host physiology pre-dating the onset of disease. This question has never been addressed. Adult height progressively increased during the last century. A clue therefore to the duration of pre-clinical changes in IBD could be obtained by studying at what age peak adult height is reached and by how much this differs from the end of the growth period (approximately 18 yrs of age for women and 22 for men). Methods: An IBD database was established at Croydon University Hospital in 2002. 717 subjects had adult height recorded. Adult height was modelled against age at diagnosis, and age at diagnosed squared to ascertain the inflexion point of the age at diagnosis vs. adult height. Significance tests were performed using ANOVA. The distance of this inflexion point from the end of puberty would give a guide to the latency period of IBD. Men and women, UC and CD were analysed separately and analyses were adjusted for age of the subject by December 2015. Results: Regression plots of age at diagnosis squared modelled against adult height were curvilinear for patients with CD, with an inflexion point at 34 years of age for females and 28 years of age for males, indicating that patients diagnosed below these ages did not reach peak expected adult height. The same effect was not seen for patients with UC in whom there was a constant trend towards shorter adult height throughout the range from younger to older. Conclusion: As predicted, patients diagnosed with CD during the pubertal period failed to reach expected peak adult height. However reduced peak adult height was also seen in patients diagnosed in young adulthood (up to 34 years in females; 28 years in males). This suggests that CD has a latent period lasting up to 20 years prior to the manifestation of symptoms, during which changes in host physiology could be acting to reduce growth in childhood. UC did not exert the same effect on peak adult height. Disclosure of Interest: None Declared